Problem Based Learning Model Assisted by Visual Media Improves Critical Thinking Skills of Grade IV Elementary School Students - Juniantari, Ni Luh Putu; Suniasih, Ni Wayan (Thinking Skills and Creativity Journal, 2023)
Learning that is still teacher-centered results in students becoming passive during the learning process. This makes students less able to think critically because of the lack of opportunity to develop their creativity. This study aims to analyze the problem-based learning model assisted by visual media on critical thinking skills for grade IV students in elementary school. The type of research used is a pseudo-experiment with a non-equivalent control group design. The population in this study were grade IV elementary school students as many as 215 students. The sample was determined by Cluster Random Sampling technique. The sample in this study in the experimental group was 30 students and in the control group was 29 students. The data collection method in this study used the critical thinking ability test method using an assessment rubric. The post-test data obtained was analyzed using t-test analysis technique with separated variance formula. Based on the analysis results, F count 1.148 and F table 1.875 at a significance level of 5% (α equals 0.05) so that the data is declared homogeneous. The conclusion of the research is that there is a significant effect of problem-based learning model assisted by visual media on critical thinking skills for grade IV elementary school students.